Rapid Detection of KPC-Producing Enterobacterales Susceptible to Imipenem/Relebactam by Using the MALDI-TOF MS MBT STAR-Carba IVD Assay - Oviaño, Marina; Gato, Eva; Bou, Germán (Frontiers in Microbiology, 2020)
KPC-producing Enterobacterales represent a serious public health concern. Limited therapeutic options are available for treatment, however the novel combination of imipenem/relebactam represents a promising alternative. To preserve the activity of this new antibiotic combination, only targeted treatments will be recommended, and rapid tests to detect susceptible bacteria are therefore urgently needed. Here, we propose a MALDI-TOF-based method using the MBT STAR-Carba IVD assay, Bruker Daltonik, to detect KPC-producing Enterobacterales susceptible to imipenem/ relebactam in a random selection of 143 clinical isolates previous molecular characterized, carrying 97 blaKPC, 1 blaGES, 12blaVIM, 4blaIMP, 3blaNDM and 26blaOXA-48-like. Species identification was confirmed by MALDI-TOF MS. The molecular characterization of the isolates was performed by the Xpert Carba-R Assay and the results were used as gold standard. Besides, all isolates were submitted to imipenem and imipenem/relebactam microdilution susceptibility testing. The assay showed an overall sensitivity and specificity to detect class A-producing Enterobacterales susceptible to imipenem/relebactam of 98 % (96/98) and 93% (42/45), respectively. This MALDI-TOF-based methodology, with a turnaround time of less than 1 hour, is a reliable test for detecting imipenem/ relebactam activity and its inclusion in routine laboratory screening would facilitate the correct use of this new combination of antimicrobials as a targeted treatment.